PROBLEMATIKA EPISTEMOLOGIS TENTANG VISI, MISI, DAN TUJUAN PENDIDIKAN ISLAM - Rijal, Syamsul (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2019)
The hegemonic challenges of Western globalization have caused serious impacts on the future of Islamic education. This reality must be realized by Muslims and more specifically those involved in the world of education. For this reason, there is an anticipatory and alternative tactical and strategic step to free themselves from the hegemonic grip of Western globalization. The conception of Islamic model education does not only see education as an attempt to "educate" only (intellectual education, intelligence), but in line with the Islamic concept of human beings and their essence of existence. Therefore, the formulation of the vision, mission and objectives of Islamic education is expected to be more problematic, strategic, anticipatory, touch the application aspects and can touch the needs of the community or use of graduates. That is, Islamic education seeks to build people and society as a whole and thoroughly (insan kamil) in all aspects of a cultured and civilized life that is reflected in the lives of pious and faithful people, democratic and independent, knowledgeable, skilled, work ethic and professional, pious charity, personality, graceful morality and moral character, capable of innovation and access to change and competitive and cooperative abilities in the global era and local thinking in obtaining world welfare and the hereafter.